Using Molasses in a Rice Straw Urea Lime Molasses Mixture to Improve Digestibility and In vitro Metabolite Fermentation - Cakra, I.G.L.O.; Trisnadewi, A.A.A.S.; Mudi, I.M.; Wibawa, A.A.P.P. (Pakistan Journal of Nutrition, 2018)
Background and Objective: The use of Rice Straw (RS) directly as a single feed not meet the nutritional needs of livestock. Inhibiting factors of using rice straw as feed for ruminants include the low content of nutrients, problems with digestibility and problems with palatability. To determine the optimal use of molasses in a rice straw Urea Lime Molasses (ULM) mixture, the effects of molasses levels were studied with the aim of improving the nutrient value, rumen metabolite content, dry matter and organic matter digestibility in vitro. Materials and Methods: The study was conducted using a completely randomized design with five treatments and four replications. The treatments were A [89% RS, 4% urea (U), 2% lime (L), 5% molasses (M)], B [84% RS, 4% U, 2% L, 10% M], C [79% RS, 4% U, 2% L, 15% M], D [74% RS, 4% U, 2% L, 20% M] and E [69% RS, 4% U, 2% L, 25% M]. The variables observed were the nutrient value, fermentation metabolite level, Rumen Dry Matter Digestibility (RDMD), Rumen Organic Matter Digestibility (ROMD), In vitro Dry Matter Digestibility (IDMD) and in vitro Organic Matter Digestibility (IOMD). Results: Adding a urea lime molasses mixture increased the nutrient value of RS in proportion to the increase in molasses usage, especially considering Crude Protein (CP). The addition of the ULM mixture to RS could increase the CP content. Similarly, the positive effects of adding the ULM to RS can be seen in metabolite fermentation, based on NH3 levels. Low levels of NH3 are due to its high utilization by rumen microbes. The IDMD and IOMD were highest in treatment E. Conclusion: The use of molasses at a concentration of 25% is the best when considering the optimal nutrient content, rumen metabolites, IDMD and IOMD.